Glomus sp. and Bacillus sp. strains mitigate the adverse effects of drought on maize (Zea mays L.) - Wilmowicz, Emilia; Kućko, Agata; Bogati, Kalisa; Wolska, Magdalena; Świdziński, Michał; Burkowska-But, Aleksandra; Walczak, Maciej (Frontiers in Plant Science, 2022)
Maize (Zea mays L.) is an economically important source of food and feed. This species is highly sensitive to drought, which is the most limiting factor for the biomass yield of a crop. Thus, maize cultivation methods should be improved, especially by environment-friendly agricultural practices, such as microorganisms. Here, we provide evidence that Glomus sp. and Bacillus sp. modulate maize response to drought. Inoculation of maize seeds by these microorganisms restored the proper photosynthetic activity of the plant under drought and stabilized the osmoprotectant content of the leaf. The beneficial effect of Glomus sp. and Bacillus sp. was also related to the stabilization of cell redox status reflected by hydrogen peroxide content, antioxidant enzymes, and malondialdehyde level in leaves. As we revealed by several methods, shaping maize response to drought is mediated by both microorganism-mediated modifications of cell wall composition and structure of leaves, such as downregulating pectin, affecting their methylation degree, and increasing hemicellulose content. Overall, we provide new information about the mechanisms by which Glomus sp. and Bacillus sp. induce drought tolerance in maize, which is a promising approach for mitigating abiotic stresses.